EVALUASI PENGGUNAAN SUPLEMEN KEHAMILAN PADA PASIEN WANITA HAMIL DI PUSKESMAS BULILI KOTA PALU PERIODE APRIL 2018 – DESEMBER 2018 - Mukaddas, Alwiyah; Hardani, Ririen; Fandi, Indra Dwi (Jurnal Ilmiah As-Syifaa, 2021)
Anemia in pregnant women will increase the risk of new born babies with low birth weight, miscarriage, premature, risk of bleeding before and / or during labor can cause death to both of them. This research aims to determine the evaluation before and after pregnancy supplement to pregnant women at Puskesmas Bulili, Palu, April - December 2018. This is a quantitative research with a retrospective approach. There are 44 females without the anemia and 22 at the anemia group. Pregnant women are said to be anemic when their hemoglobin or red blood levels are less than 11.0 gr%. The results, the hemoglobin levels before and after the use of pregnancy supplements in the non-anemia were 11.7 gr / dl and 11.4 gr dl (p = 0.004; p <0.005), the anemia group 9.7 gr / dl and 11 , 3 gr / dl (p = 0.000; p <0.005, there was a significant change in hemoglobin level. The results showed no anemia group difference which smaller (0.3 g / dl) compared to the anemia group (1.6 g / rdl), with values (p = 0.317; p> 0.005) which means no significant difference in hemoglobin levels after pregnancy supplementation